ANALYSIS OF FINANCING RESTRUCTURING DURING THE COVID-19 PANDEMIC IN THE SHARIA BUSINESS UNIT (UUS) of PT. SUMUT BANK - Jaya, Abdi; Julianti Nasution, Yenni Samri; Dalimunthe, Ahmad Amin (Moneter: Jurnal Keuangan dan Perbankan, 2023)
Covid-19 pandemic that has hit the world has resulted decline economics and influence sector banking in a manner general including banking sharia experience decline growth , consequently banking sharia must do way to be healthy still awake and able relieve burden customers affected . Efforts made by the Sharia Business Unit of PT Bank Sumut in framework help customers so they can finish one of the obligations do Restructurisation Financing refers to OJK Regulation No. 11/POJK.03/2020 concerning National Economic Stimulus as Policy Countercyclical Impact Spread of Coronavirus Disease 2019. As for restructuring financing This specialized to business customers _ affected the Covid-19 pandemic is good in a manner direct nor No direct However Still own prospect For finish his obligations after restructured . Study This own objective For analyze application restructuring and its obstacles in settlement financing during the covid-19 virus pandemic in the Sharia Business Unit of PT. North Sumatra Bank . Method study use use approach method qualitative For analyze in a manner descriptive with use approach analysis SWOT . Objective study This There is two namely (1) Knowing How mechanism application restructuring during the Covid-19 pandemic at UUS PT Bank Sumut that is through rescheduling and reconditioning ; (2) Knowing obstacle in implementation restructuring during the Covid-19 period at UUS PT Bank Sumut that is related with weakness analysis restructuring , lack information about accepted restructuring _ customers and difficulties customers in fulfil completeness file application restructurisation